Metal sulfide nanoparticle-based dual barcode-triggered DNAzyme cascade for multiplex miRNA detection in a single assay. Issue 44 (1st November 2022) - Wang, Jiao; Wen, Liyuan; Cao, Ruyuan; Gao, Xiaorong; Li, Xia; Xu, Ensheng; Zhang, Qi; Xu, Shuling; Dai, Caifeng; Xue, Qingwang
Abstract : A metal sulfide nanoparticles-based dual bar-codes triggered DNAzyme cascade strategy was developed for sensitive and simultaneous multiplex miRNA detection in a single assay. Abstract : Single miRNAs are not specific and accurate enough to meet the strict diagnosis requirements in practice. Therefore, simultaneous monitoring of multiplexed miRNA in biological samples can not only improve the accuracy and specificity of bioassays but also avoid the squandering of valuable biological specimens. Herein, we designed a metal sulfide nanoparticle-based dual barcode-triggered DNAzyme cascade strategy for the sensitive and simultaneous multiplex miRNA detection in a single assay. Firstly, the capture probes (H1, H2) specifically recognize targets (miRNA-21, miRNA-141), exposing the stem of H1 and H2. Then, with the introduction of a detection probe (CuS-H3, ZnS-H4), the exposed H1 and H2 catalyze the hairpin assembly (CHA) reaction, realizing target miRNA recycling, and forming H1/H3-CuS and H2/H4-ZnS complexes. Subsequently, the formed H1/H3-CuS and H2/H4-ZnS complexes are encoded on magnetic beads through the biotin/streptavidin interaction. The CuS and ZnS nanoparticles captured by magnetic beads release thousands of Cu 2+ and Zn 2+ via the cation exchange reaction. Finally, the released Cu 2+ and Zn 2+ specially activate the DNAzyme of the catalytic and molecular beacon (CAMB) system. The CAMB system affords an amplified fluorescence signal output by cycling and regenerating the metal ion-dependent DNAzyme to realize multiple enzymatic turnovers. Benefiting from target recycling, nanoparticle amplification, and catalytic and molecular beacon amplification, there is substantial amplification and the target miRNAs can be detected at 0.06 fM (miRNA-21) and 0.048 fM (miRNA-141) in a single assay. Furthermore, the high selectivity and accuracy of the assay were proved by practical analysis of different cancer cells, which exhibited good practicability in multiplex miRNA detection in clinical sera. The results indicate that the proposed strategy holds great potential for the sensitive detection of multiplex cancer biomarkers and offers the opportunity for future applications in clinical diagnosis.